Relative Tolerance of Crops to Surface Water Stagnation - Gupta, S K; Sharma, D P; Swarup, Anand (Journal of Agricultural Engineering, 2004)
Water stagnation in cropped lands is assuming a serious dimension particularly in canal irrigation commands due to its adverse effects on crop growth. In order to assess the drainage requirement of commonly grown crops, a study was undertaken to assess the relative tolerance of 8 crops to water stagnation. It has been shown that under normal agro-climatic conditions with short-term water stagnation, the crop yields were adversely affected because of poor aeration resulting in reduced uptake of plant nutrients especially N, P, K and Zn. Toxicity effects of Fe and Mn were not encountered. Under these conditions, data revealed that water stagnation must be removed from the crop land within one day for sunflower, wheat and mustard, within two days for sorghum, pearl millet, pigeon pea and berseem (seed) and within 3-4 days for barley. Apparently, barley is the most tolerant to water stagnation amongst the tested crops while wheat, mustard and sunflower are the least tolerant. Since wheat is grown over large areas, need of a good drainage system is apparently highlighted.